SOMATIC COMORBIDITY AMONG MEN AND WOMEN WITH STABLE ANGINA - M. N. Mamedov; R. T. Didigova; Z. O. Ugurchieva (Российский кардиологический журнал, 2016)
Aim. To assess somatic comorbidity in male and female cohort with stable angina (sA). Material and methods. Into multicenter,  simlutaneous  cohort-clinical study, 300 men included (mean  age  54±0,4 y.o.) and 230 women (mean  age  55,7±0,5  y.o.) with sA  of  I-III  functional  class.  four  institutions  participated   from  Ingushetia Republic.  Clinical and  instrumental  assessment included  anthropometry, office blood pressure, heart rate, eCG in 12 leads recording.  In fasting venous blood we measured total cholesterol (mM/L) and glucose (mM/L).Results. In cohort of patients with sA the most prevalent are cholelythiasis, gastric and duodenal ulcer disease, chronic diseases of pancreas, separately  or together; chronic bulbitis is found in each third person,  and urinary lythiasis in 15% of cases. Gastric ulcer and duodenal  ulcer diseases, chronic bronchitis and urinary lythiasis are  two times more prevalent  in men compare  to women, but cholelythiasis and chronic diseases of pancreas show the same  prevalence  among men and women.Among women with sA thyroid diseases are 3 times more prevalent than in men.Conclusion. so, in sA patients  comorbidity is quite common.  Management and prevention in sA patients cohort should be multifactorial taken a broad spectrum  of social and demographic parameters, main risk factors and comorbidities.  The key role in coordination  and realization of all these  activities should be granted  to an internist of broad spectrum  or general care physician.